Systemic PAI Curriculum Integration Model: Synchronizing Educational Pathways Within a Deep Learning Framework Based on Graduate Profiles - Durrotun Nafisah; Mashudi Mashudi; Dyah Nawangsari; Ubaidillah Ubaidillah (AFKARINA: Jurnal Pendidikan Agama Islam, 2025)
Minister of Primary and Secondary Education Regulation Number 13 of 2025 directs the national curriculum toward a deep learning approach with a primary focus on the intracurricular path. However, the regulation does not yet technically govern the integration mechanism between intracurricular, co-curricular, and extracurricular paths. This condition results in a policy gap and policy vacuum that leads to the fragmentation of students' learning experiences in the field. This qualitative research, utilizing literature study and policy analysis, aims to examine this policy gap and formulate a systemic curricular integration model. The findings indicate that the absence of integration regulations results in the repetition of learning materials, which hinders the achievement of deep learning and creates administrative excesses for teachers in the form of duplicated planning and assessment documents. As a solution, this study proposes the Systemic Curriculum Integration Model, which consists of three main components: integrated planning (One-Door system), a material bridging matrix across paths to ensure a spiral curriculum, and comprehensive assessment. This model is expected to create curricular synchronization that alleviates the administrative burden on teachers while optimizing the holistic formation of the eight dimensions of graduate profiles. The study recommends the issuance of supplementary policies by the Ministry of Primary and Secondary Education and the Ministry of Religious Affairs to address the technical regulatory void regarding this integration.